Implication of Genetic Deletion of Wdr13 in Mice: Mild Anxiety, Better Performance in Spatial Memory Task, with Upregulation of Multiple Synaptic Proteins - Mitra, Shiladitya; Sameer Kumar, Ghantasala S.; Tiwari, Vivek; Lakshmi, B. Jyothi; Thakur, Suman S.; Kumar, Satish (Frontiers in Molecular Neuroscience, 2016)
WDR13 expresses from the X chromosome and has a highly conserved coding sequence. There have been multiple associations of WDR13 with memory. However, its detailed function in context of brain and behavior remains unknown. We characterized the behavioral phenotype of two months old male mice lacking the homologue of WDR13 gene (Wdr13-/0). Taking cue from analysis of its expression in the brain, we chose hippocampus for molecular studies to delineate its function. Wdr13-/0 mice spent less time in the central area of the open field test and with the novel object in novel object recognition test as compared to the wild-type. However, these mice didn’t show any significant changes in total time spent in arms or frequency of arm entries in elevated plus maze. In the absence of Wdr13, there was a significant upregulation of synaptic proteins, viz., SYN1, RAB3A, CAMK2A etc accompanied with increased spine density of hippocampal CA1 neurons and better spatial memory in mice as measured by increased time spent in target quadrant of Morris water maze during probe test. Parallel study from our lab has established c-JUN, ER α/ β and HDAC 1,3,7 as interacting partners of WDR13. WDR13 represses transcription from AP1 (c-JUN responsive) and ERE (Estrogen Receptor Element) promoters. We hypothesized that absence of Wdr13 would resulted in de-regulated expression of a number of genes including multiple synaptic genes leading to the observed phenotype. Knocking down Wdr13 in Neuro2a cell lines led to increased transcripts of Camk2a and Nrxn2 consistent with in-vivo results. Summarily, our data provides functional evidence for the role of Wdr13 in brain.